(untitled) (Annual of the Faculty of Philosophy in Skopje, 2021)
The Friendship Treaty between Sofia and Skopje was one of the first foreign policy achievements of the newly formed Zoran Zaev-led government in 2017. It was presented as a closure of the long-lasting bilateral dispute between the two neighbouring countries, which would remove one obstacle on the way to EU integration. However, the subsequent Prespa agreement (signed almost a year later) took all the glory and public attention. The Friendship Treaty’s real political weight and imperfections became obvious only in December 2020, when the Bulgarian veto prevented the opening of the negotiation process for the country. The article analyses and evaluates the Treaty and its implication through the political and legal lenses. The basic premise is that instead of paving the way to the full EU membership, the hastily signed agreement proved to be not only a new obstacle on the road but also a factor of deepening mutual distrust and tensions between the two peoples. The twist with the introduction of the new methodology of EU enlargement along with the Bulgarian veto makes the Balkan entanglement even more complex. The Macedonian state is back to square one, just like in the dispute with Greece, now being knotted with another bilateral dispute and identity issues that have nothing to do with good neighbourly relations and/or Copenhagen criteria. Conversely, this downplayed dispute may have a strong impact on the Macedonian state’s viability in the mid- and long run. The key conclusion is that the stalemate of the EU enlargement process is at the same time a cause and a consequence of Brussel’s inability to understand and resolve the protracted conflicts in the Balkans as well as a proof that EU membership is not a panacea for the age-old nationalism and chauvinism.